Errata corrige: Med Lav 2016;107(3):235-242 - P. Petromilli Nordi Sasso Garcia, C. Dupim Presoto, J. Maroco, J. Alvares Duarte Bonini Campos - Work-related activities that may contribute to musculoskeletal symptoms among dental students: validation study - Redazione, La (La Medicina del Lavoro, 2016)
The authors reported an error that need to fully replace the data already published. The mistake is in Table 2 and the incorrect information may interfere with the results’ interpretation, taking the reader to error. The values of factor 1 (Repetitiveness) should be in the first column, not in the third, corresponding to Q1, Q2, Q3 and Q4 items. The values of Factor 2 (Working Posture) should be in the second column, not in the first, corresponding to Q5, Q6, Q7, Q8 and Q9 items. The values of Factor 3 (External Factors) should be in the third column, not in the second, corresponding to Q9, Q10, Q11, Q12, Q13, Q14 and Q15. Therefore, the authors requested an erratum in order to allow a real understanding by the readers of the information presented. The new table with corrections is presented below. Table 2 - Structural matrix with varimax orthogonal rotation of the factors* of the "Questionnaire on work-related activities that may contribute to musculoskeletal symptoms". [...]